Methylation status of selected genes in non-small cell lung carcinoma - current knowledge and future perspectives - Put, Adam; Smesny Trtkova, Katerina; Skarda, Jozef (Neoplasma, 2024)
DNA methylation is recognized as an early event in cancer initiation and progression. This review aimed to compare the methylation status of promoter regions in selected genes across different histological subtypes of non-small cell lung cancer (NSCLC), including adenocarcinoma, squamous cell carcinoma, large cell carcinoma, and the rare but highly aggressive large-cell neuroendocrine carcinoma (LCNEC). A comprehensive literature search was conducted in the PubMed database until August 17, 2024, using standardized keywords to identify reports on promoter methylation in NSCLC. Seventy-five studies were reviewed, focusing on the promoter methylation of key genes, such as APC, BRCA1, CDH1, CDH13, DAPK1, DLEC1, FHIT, GSTP1, hMLH1, MGMT, CDKN2A, RARβ, RASSF1, RUNX3, and TIMP3. These studies explored diagnostic, prognostic, epidemiological, and therapeutic aspects across NSCLC subtypes. Additionally, mutational profiles of TP53, RB1, KEAP1, and STK11 and expression patterns of ASCL1, DLL3, and NOTCH were analyzed. The findings suggest that LCNEC may serve as a biological bridge between non-small cell and small-cell lung carcinoma. Our analysis highlights that the methylation status of selected genes could enhance diagnosis, prognosis, and personalized treatment strategies in patients with NSCLC, particularly those with LCNEC.
Keywords: DNA Methylation; promotorové oblasti (genetika); Promoter Regions, Genetic; nádory plic; nemalobuněčný karcinom plic; prognóza; nádorové biomarkery; Humans; Gene Expression Regulation, Neoplastic; metylace DNA; Lung Neoplasms; Carcinoma, Non-Small-Cell Lung; Prognosis; lidé; regulace genové exprese u nádorů; Biomarkers, Tumor